Grado de depresión según la Escala de Yesavage en los adultos mayores institucionalizados en el Hogar de Ancianos Esteban Quirola de la cuidad de Machala. - Paucar Aguilar, Diana C. (2014)
The object of this study was to determine the degree of depression that is going through the institutionalized elderly in the nursing home Esteban Quirola city of Machala. The type of study is cross-sectional, descriptive information is obtained by carrying out a survey of institutionalized elderly which contained the same variables as age, gender, and yesavage scale. We studied a total of 48 patients over 60 years. The results were: The entire study sample 92% which is the highest percentage showed some degree of depression, older adults institutionalized in nursing home Esteban Quirola 71% is male compared with 29% of females.